Botulinum Toxin Type A for the Treatment of Skin Ulcers: A Review Article - Waranaree Winayanuwattikun (2022)
The normal biological wound healing process consists of three precisely and highly programmed phases that require optimal conditions including internal and external factors. Any negative factors that disrupt the sequence or time frame of the healing mechanism can result in a non-healing wound or chronic ulcers. Botulinum neurotoxin A (BoNT-A) which is generally known as anti-contraction of muscles has been reported as a successful treatment in various types of chronic ulcers. The aim of this study is to review the outcome of treatment with BoNT-A for chronic skin ulcers. The results demonstrated some positive effects of BoNT-A on chronic ulcers. Ischemic ulcers secondary to Raynaud’s phenomenon seem to be the most promising type of ulcers that have benefited from BoNT-A. The rationale behind using BoNT-A to fasten the wound healing process is also discussed. Further clinical trial studies should be conducted to affirm the efficacy of wound healing using BoNT-A administration.